2019
DOI: 10.1111/jace.16669
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative prediction of the structure and luminescence properties of Nd3+ doped borate laser glasses

Abstract: Although great advance has been made in glass science, predicting luminescence properties of laser glass poses a significant challenge for scientists due to the complex relationship between the composition, structure, and properties of the rare earth ions doped laser glasses. The development of high‐performance laser glass usually relies on intuition and trial‐and‐error. Recently, with the proposal of the materials genome engineering, the “glass genome” has also attracted much attention. Here, the structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This method is based on the basic theory of glass formation and avoids complex calculation coefficients in traditional additive methods. Previous works in our laboratory also proved that the structure and properties of laser glasses can be accurately predicted to a certain extent through this method 19–23 …”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…This method is based on the basic theory of glass formation and avoids complex calculation coefficients in traditional additive methods. Previous works in our laboratory also proved that the structure and properties of laser glasses can be accurately predicted to a certain extent through this method 19–23 …”
Section: Introductionmentioning
confidence: 65%
“…Previous works in our laboratory also proved that the structure and properties of laser glasses can be accurately predicted to a certain extent through this method. [19][20][21][22][23] In this study, we aim to further study the adaptability and accuracy of this method for traditional laser glasses, such as silicate, phosphate, and borate glasses, particularly for the prediction of their spectroscopic properties. All these glass systems are derived from main components of commercial laser glasses commonly used in 1 μm solid laser and fiber laser.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches have successfully decoded the “glass genome” at different scales. Previously, we demonstrated that the glass‐forming ion‐centered coordination polyhedron of the resulting glass is similar to the coordination polyhedron of the neighboring glassy congruent compounds of the glass, which can be considered as the “glass genes.” 21,22 Moreover, the structure and luminescence properties of multicomponent oxide laser glasses have been quantitatively predicted based on the “glass genes.” 1,21,22 Nevertheless, this method lacks physical interpretation. In addition, this method is not suitable for all multicomponent oxide glass systems because some neighboring glassy congruent compounds of multicomponent oxide glass may not be possibly prepared by using the conventional melt‐quenching.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated that the glass-forming ioncentered coordination polyhedron of the resulting glass is similar to the coordination polyhedron of the neighboring glassy congruent compounds of the glass, which can be considered as the "glass genes." 21,22 Moreover, the structure and luminescence properties of multicomponent oxide laser glasses have been quantitatively predicted based on the "glass genes." 1,21,22 Nevertheless, this method lacks physical interpretation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation